Temperature fluctuations in a nonisothermal mercury pipe flow affected by a strong transverse magnetic field. (December 2018) - Belyaev, Ivan; Frick, Peter; Razuvanov, Nikita; Sviridov, Evgeniy; Sviridov, Valentin
Highlights: Different liquid metal flow patterns are observed in transverse magnetic field. Temperature fields are used to reveal flow hydrodynamics. Flow fluctuations are possible in the flow affected by strong magnetic field. Criteria to generalize flow patterns are chosen. Abstract: Liquid metal flows in rectangular ducts and circular pipes under high thermal loads and strong transverse magnetic fields are of great interest in context of developing cooling systems for fusion reactors. In this study, a downward flow of mercury in a uniformly heated pipe affected by a transverse magnetic field is studied experimentally. We show that moderate magnetic fields (0.2–1 T; Hartmann numbers 100–500) not only do not suppress the temperature fluctuations, but lead to the existence of significantly different regimes, characterized by strong temperature fluctuations. At least two different states of fluctuating flow exist. These states generate quantitatively different patterns of temperature fluctuation characteristics in the pipe cross-section. Domains of existence of both regimes are localized in the parameter plane Richardson versus Hartmann numbers. It is shown that these regimes are controlled by the Richardson number and disappear at high Hartmann numbers (above 500).